2018
DOI: 10.19082/68
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of and attitude towards blood donation in students at the Semnan University of Medical Sciences

Abstract: Background: Despite the increasing demands for blood and its products, some people, especially the youth, have little interest in donating blood. Objective: This study aimed to assess the university students' awareness of and attitude towards blood donation. Methods: In this cross-sectional study, a descriptive analytical approach was used to examine awareness of and attitude towards blood donation among students in Semnan University of Medical Sciences, Semnan, Iran. The study was performed in 2015-2016. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 15 publications
7
22
2
2
Order By: Relevance
“…The findings observed in this study lay in the middle of the finding of previous studies that have examined the blood donation practice among university students in different parts of Africa 55.4%, 45.8%, 30%, 22.9%, 12.5%, and 9.74% 8 , 12 ,16,17,21, 22 and community-based studies 53.3%, 22.6% to 16.1%. 9 , 11 , 15 The study also further identified only 60 (42.3%) repeated blood donor compared to 55% of in University students in Tanzania.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The findings observed in this study lay in the middle of the finding of previous studies that have examined the blood donation practice among university students in different parts of Africa 55.4%, 45.8%, 30%, 22.9%, 12.5%, and 9.74% 8 , 12 ,16,17,21, 22 and community-based studies 53.3%, 22.6% to 16.1%. 9 , 11 , 15 The study also further identified only 60 (42.3%) repeated blood donor compared to 55% of in University students in Tanzania.…”
Section: Discussionsupporting
confidence: 76%
“… 10 , 11 A study among University students in Iran, in 2018 stated that study participants had 23.6% negative, 58.7% moderate, and only 17.7% good attitude towards blood donation. 12 Similarly, communitybased studies from Ethiopia found 52.2% and 32.9% of favorable attitude towards blood donation. 9 , 11 However, a study conducted at Gondar town Northwest Ethiopia in 2016 identified 82% good attitude towards blood donation, which had huge difference from other similar studies.…”
Section: Introductionmentioning
confidence: 96%
“…22 Whereas, another study by Gebresilase H. W. et al reports religion to be one of the significant predictors of knowledge regarding blood donation among students. 23 Similarly, 6% and 7.6% of non-donors indicated religion and cultural belief as to the barrier for not donating blood before, as reported by Javaeed A. et al 14 , and Ugwu N. I. et al 7 respectively. Our study population consists of the Hindu population mostly, and there were no reported restrictions imposed by the Hindu community over blood donation practice.…”
Section: Discussionmentioning
confidence: 77%
“…A study conducted by Ugwu N. I. et al in Nigeria among medical students reports that 69.6% of blood donors have only donated once, and 16% donated twice before. 7 Also, in another study, there were only 13.6% of students as regular blood donors. 8 Tariq S. et al also reported that 8.7% of donors are one time donors among medical students.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation